Valentino - Steiger, Brad; Mank, Chaw; Grofé, Ferde 1892-1972; Black, Stanley 1913-2002 (Metro-Goldwyn-Mayer Studios, 2016)
"Das Leben des berühmten Stummfilm-Stars Rudolph Valentino (1895-1926) in einer sehr subjektiven, ausschweifend fantasievollen Darstellung. [...]" [filmdienst.de]
Original: Großbritannien, USA 1976
Special features: presented in both high definition and standard definition, audio commentary with Tim Lucas, original TV spots and trailers, Dudley Sutton remembers Ken Russell and filming Valentino (2016, 22 mins), the Guardian Lecture: Ken Russell in conversation with Derek Malcolm (1987, 89 mins), Lynn Seymour remembers Rudolf Nurevey (2003, 9 mins, audio with stills), tonight: Nureyev on Ken Russell and Valentino (1977, 10 mins), stills and special collections gallery (2016, 10 mins), the funeral of Valentino (1926, 9 mins), textless opening and closing credits, isolated music and effects track, fully illustrated booklet with extensive credits and newly commiddioned essays
Keywords: Film